Values of Character Education in Nyirok Tradition of Negara Batin Customary Community and Its Implications in the Local Wisdom and Ethics Education Course - Aryani, Farida (Jurnal Pendidikan Progresif, 2020)
Values of Character Education in Nyirok Tradition of Negara Batin Customary Community and Its Implications in the Local Wisdom and Ethics Education Course. Objectives : The aim of this paper is to document the ethical values that exist in cultural behaviour, in nyirok tradition in particular. Method: This study is descriptive in nature which was conducted through a qualitative approach. The data were collected through document analysis, audio-video recordings, and interviews. Findings: The study found five confessions revealed through the jewelry attachment ceremony in the form of ali, bracelets, eardrops, chains, jungsarat fabrics and seven-color ropes. At the time of the attachment in each stage it is followed by an oral tradition in the form of utterances called pisaan. Nyirok tradition has educational values. The educational values that are embodied in the procession of jewelry attachment in the tradition include expressions of love, acknowledgment of belonging, friendship, empathy, sincerity, and responsibility. Conclusions: This nyirok tradition can be used as knowledge for students in the development of both oral tradition and character values knowledge.Keywords: character education, local wisdom, ethics education, customary community, nyirok.DOI: 10.23960/jpp.v10.i1.202005